PROSES KARBURASI PADAT PADA BAJA KARBON RENDAH DENGAN TEMPERATUR 900 C, 1000 C, DAN 1100 C - Helanianto, Helanianto; Rahmadi, Hairian (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2023)
This study aims to determine the effect of temperature on the solid carburizing on increasing the hardness value of ST37 steel. This solid carburizing uses temperature variations of 9000C, 10000C and 11000C, with a holding time of 30 minutes. The material used is a mixture of CaCO3 and coconut shell charcoal with mineral water as a cooling medium. The test carried out was the Rockwell hardness test which was carried out in the Mechanical Engineering Materials Testing Lab of Politeknik Negeri Ketapang. From the test results for ST37 steel, the average hardness obtained in the raw material = 48.3 HRB, then in each carbonation treatment at a temperature of 9000C = 48.6 HRB, a temperature of 10000C = 48.9 HRB, a temperature of 11000C = 49.1 HRB. Carburized steel plates with a temperature of 9000C, 10000C and 11000C the test results are harder than the raw material.